Efficient negative oxygen ion membrane and preparation process thereof
By introducing electron resonance layer and nano tourmaline layer into the negative oxygen ion film, and activate the charge in tourmaline by using carbon fiber web and thin-film solar cells, the problem of limited release range of existing negative oxygen ion films is solved, and more efficient negative oxygen ion release and longer service life are achieved.
Patent Information
- Application Number
- CN202510053739.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
When used, the existing negative oxygen ion membranes have a relatively close range of diffusion, and cannot efficiently release negative oxygen ions, which cannot meet the needs of certain occasions.
A high-efficiency negative oxygen ion film consisting of an electron resonance layer and a nano tourmaline layer is used. The electron resonance layer includes a grid-shaped carbon fiber web and thin-film solar cell. The tourmaline in the nano tourmaline generates charge under magnetic field, temperature changes or mechanical pressure, and activates molecules to release more negative oxygen ions.
The longer-range release of negative oxygen ions is achieved, the release efficiency of negative oxygen ions is improved, the insulation performance and strength of the film is enhanced, and the service life is extended.
Smart Images

Figure CN119840278A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional new materials, and in particular to a high-efficiency negative oxygen ion membrane and a preparation process thereof. Background Art
[0002] Negative ions are a kind of far-infrared radiation material that is very beneficial to human health. The best wavelength of far-infrared rays suitable for human absorption is 9.6μm. The far-infrared rays radiated by negative ion mineral crystals are well coordinated with the human body and can be completely absorbed by the human body. For each positive and negative ion, its life span is short, generally only exists for tens of minutes. The amount of negative ions in the air varies depending on the particularity of geographical conditions. There are more negative ions in parks, suburban fields, seashores, lakes, waterfalls and forests. When people enter the above venues, their minds are refreshed and their breathing is comfortable and refreshing. Entering a noisy and crowded crowd or an air-conditioned room makes people feel stuffy and have difficulty breathing. Generally speaking, people need about 13 billion negative ions every day, while living rooms, offices, entertainment venues and other environments can only provide about 100 million to 200 million. This huge contrast between supply and demand often leads to respiratory diseases such as pneumonia and tracheitis. Negative oxygen ions have the functions of killing bacteria, purifying air, anti-oxidation, anti-aging, and removing free radicals in the body. They are beneficial to the physical and mental health of the human body and are known as "air vitamins." The concentration of negative oxygen ions in the air is one of the indicators of air quality.
[0003] Therefore, the research on the preparation of materials that release negative oxygen ions efficiently has received extensive attention. Tourmaline, opal, six-ring stone, and strange ice stone, which have the function of releasing negative oxygen ions, have been widely studied in existing patents. Tourmaline, in particular, has a permanent spontaneous polarization effect and can continuously stimulate the release of negative oxygen ions, thus being widely used in various fields as a healthy and environmentally friendly negative oxygen ion release material.
[0004] Tourmaline has an electrostatic field around it, which can electrolyze water molecules in the electric field to form charged ions, among which the negatively charged ions combine with oxygen molecules in the air to form negative oxygen ions. However, the concentration of negative oxygen ions produced by tourmaline itself cannot meet the needs of many specific occasions, and further modification is needed to improve its ability to stimulate the production of negative oxygen ions.
[0005] At present, the performance of materials that release negative oxygen ions is improved by refining the particle size and adding various types of modifiers when using tourmaline as the base material. However, as the particle size of the powder decreases, the specific surface area increases, and the specific surface energy increases, agglomeration is easily generated during the preparation and processing, making it difficult for tourmaline to be evenly dispersed during the composite process with other components, thereby affecting the comprehensive performance and service life of the composite material.
[0006] At the same time, when the existing negative oxygen ion membrane is in use, the diffusion range of negative oxygen ions is relatively short, and negative oxygen ions are not released to places far away in the room, and the effect of efficiently releasing negative oxygen ions cannot be achieved.
[0007] Therefore, studying a preparation method for efficiently releasing negative oxygen ions has very important application prospects. Summary of the invention
[0008] One object of the present invention is to provide a high-efficiency negative oxygen ion membrane and a preparation process thereof, so as to activate the molecules in the membrane and make it release more negative oxygen ions.
[0009] This purpose is achieved by adopting the following technical solutions:
[0010] A high-efficiency negative oxygen ion membrane and a preparation process thereof, comprising an electron resonance layer and a nano-tourmaline layer from bottom to top, wherein the electron resonance layer comprises a grid-shaped carbon fiber net, a plurality of thin-film solar cells are arranged on the carbon fiber net, and electrodes of the plurality of thin-film solar cells are respectively connected to the carbon fiber net. Preferably, the plurality of thin-film solar cells are arranged at the cross of the carbon fiber net. The contact area between the thin-film solar cell and the carbon fiber net is larger, which is more conducive to the interaction between the thin-film solar cell and the carbon fiber net.
[0011] Specifically, the nano-tourmaline layer includes tourmaline. Tourmaline is conductive, but its conductivity is relatively weak, mainly because the ionic and covalent bond structures inside the tourmaline cause the movement of charges in the crystal to be hindered to a certain extent. However, under certain conditions, such as magnetic field, temperature change or mechanical pressure, the ions or electrons in the tourmaline will move, thereby forming an electric current. Specifically:
[0012] When the tourmaline in the nano-tourmaline layer is subjected to pressure, equal and opposite charges will be generated at both ends of the tourmaline. This phenomenon is called the piezoelectric effect. Both ends of the tourmaline will be charged, so it has the phenomenon of electrostatic dust attraction.
[0013] The tourmaline in the nano-tourmaline layer also generates electric charge when heated, a phenomenon known as the thermoelectric effect. When the tourmaline is heated or cooled, equal and opposite charges are generated along the two ends of its crystal, an effect that enables the tourmaline to excite and transfer charges during the heating process.
[0014] Tourmaline in the nano-tourmaline layer will show conductivity in a magnetic field due to its special crystal structure and chemical composition. There are a large number of ions and vacancies inside the tourmaline crystal. Under the action of the magnetic field, these ions will move and form an electric current. At the same time, the conductive elements contained in tourmaline, such as copper and iron, also further enhance its conductivity. The magnetic field strength is one of the key factors affecting the conductivity of tourmaline. The stronger the magnetic field, the faster the ions in the tourmaline move, and the better the conductivity.
[0015] The tourmaline in the nano-tourmaline layer has a spontaneous polarization effect, which is manifested as an electrostatic field with the c-axis plane as the two poles around the tourmaline crystal. When the tourmaline is in a magnetic field, its polarization effect may be affected to a certain extent, thereby changing the electric field distribution around the tourmaline.
[0016] Therefore, the weak electromagnetic field and thermoelectric field effects generated by thin-film solar cells can activate the molecules in the nano-tourmaline layer, causing the nano-tourmaline layer to release more negative oxygen ions.
[0017] In addition, the carbon fiber mesh has good electrical conductivity and thermal stability. Since the nano-tourmaline layer has certain electrical conductivity, it is connected with the electrical conduction path on the carbon fiber mesh to form a loop, and the nano-tourmaline layer will generate weak electromagnetic field and thermoelectric field effects.
[0018] Therefore, on the basis that the nano-tourmaline layer is prompted to release more negative oxygen ions under the action of the thin-film solar cell, the carbon fiber mesh and the nano-tourmaline layer are connected together to form a loop, which can further prompt the nano-tourmaline layer to release more negative oxygen ions.
[0019] Secondly, when the carbon fiber net is subjected to heat energy, its surface electrons will obtain enough energy to break free from the bondage and form free electrons. These free electrons will combine with oxygen molecules in the air to form negative oxygen ions. Therefore, the range of negative oxygen ions released by the nano-tourmaline layer of the negative oxygen ion membrane of the present invention is farther than that of the existing negative oxygen ions.
[0020] On the other hand, the carbon fiber mesh has excellent thermal insulation performance and strength. Traditional thermal insulation materials have limitations in weight, thickness and cost. The carbon fiber mesh not only improves the thermal insulation performance and strength of the negative oxygen ion membrane, but also effectively reduces the thickness and cost of the negative oxygen ion membrane.
[0021] In addition, the carbon fiber mesh converts thermal energy into negative oxygen ion energy, increases the oxygen ion concentration, effectively blocks external heat transfer, and improves environmental comfort.
[0022] Furthermore, a thin-film solar cell is a photoelectric conversion device that can directly convert sunlight into electrical energy, and is mainly composed of a transparent conductive film, a thin-film solar cell element, and a back electrode. Among them, the transparent conductive film is the key part of the thin-film solar cell, which determines its transparency and photoelectric conversion efficiency. The transparent conductive film has the characteristics of high transmittance and low resistivity; the thin-film solar cell has high light transmittance, which can transmit part of the sunlight and absorb part of the light for photoelectric conversion; the thin-film solar cell has good power generation performance under weak light conditions, and can still maintain a high power generation efficiency under low light intensity. Preferably, the mesh area in the carbon fiber mesh is larger than the area of the thin-film solar cell.
[0023] Therefore, the negative oxygen ion membrane of the present invention has a light-transmitting effect in the thin-film solar cell. At the same time, in order to provide a light-transmitting effect at the carbon fiber mesh, the inventors set an optically conductive silver glue layer on the carbon fiber mesh, and the optically conductive silver glue layer is connected to the electrode of the thin-film solar cell.
[0024] The optical conductive silver glue layer is added with high-refractive glass beads and conductive silver powder materials, which has unique high conductivity and high light refractive index characteristics, making up for the defect of partial light transmittance efficiency affected by the carbon fiber mesh.
[0025] On the other hand, a PET film layer is connected below the electron resonance layer, a polyurethane film layer is connected above the nano-tourmaline layer, and a protective layer is connected above the polyurethane film layer.
[0026] Furthermore, a preparation process of a high-efficiency negative oxygen ion membrane comprises the following steps:
[0027] A single or multiple carbon fiber filaments and resin are continuously injected into a 3D printer, and printed into a grid shape on a PET film layer to obtain a carbon fiber mesh;
[0028] The back of the thin-film solar cell is coated with adhesive and pasted on the cross of the carbon fiber mesh, with the electrode of the thin-film solar cell facing upward;
[0029] The optical conductive silver paste material is printed on the carbon fiber mesh by using a 3D printer, and the optical conductive silver paste material is respectively connected to the electrodes of the thin film solar cell to obtain an electronic resonance layer;
[0030] A negative oxygen ion membrane is obtained by connecting a nano-tourmaline layer to the electron resonance layer.
[0031] Preferably, the nano-tourmaline layer comprises the following preparation steps:
[0032] Preparation of tourmaline ultrafine powder;
[0033] After fully mixing tourmaline ultrafine powder, cerium oxide, yttrium oxide, neodymium oxide and titanium dioxide, calcining at high temperature to obtain a semi-finished product, and crushing the semi-finished product to obtain high negative ion tourmaline powder;
[0034] The high negative ion tourmaline powder, alcohol-water mixture, nanocellulose, silicon oxide, menthol solution and essence solvent are uniformly mixed, and the tourmaline transparent slurry is obtained by ball milling;
[0035] The tourmaline transparent slurry is coated on the electron resonance layer to obtain a nano tourmaline layer.
[0036] Preferably, a polyurethane film layer and a protective layer are sequentially connected to the nano-tourmaline layer to obtain a negative oxygen ion membrane.
[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0038] The present invention discloses a high-efficiency negative oxygen ion membrane and a preparation process thereof. The present invention creatively adopts the technical principle of thin-film solar cells to generate weak electromagnetic fields and thermoelectric field effects. Tourmaline produces polarization effect and conductive performance under the action of a magnetic field, produces thermoelectric effect under the action of temperature changes, and produces piezoelectric effect under the action of mechanical pressure, which can further excite charges, increase the ion movement speed in the tourmaline, and further increase the release of negative oxygen ions, so that negative oxygen ions are present in a wider range.
[0039] At the same time, the present invention uses thin-film solar cells, which have high light transmittance and can transmit part of the sunlight while absorbing part of the light for photoelectric conversion. In addition, thin-film solar cells have good power generation performance under weak light conditions and can still maintain high power generation efficiency under low light intensity.
[0040] Secondly, the carbon fiber mesh has good electrical conductivity and thermal stability. When the carbon fiber mesh is subjected to thermal energy, its surface electrons will obtain sufficient energy to break free from the bondage and form free electrons. The present invention heats the carbon fiber mesh with thin-film solar cells to generate electricity, prompting the carbon fiber mesh to generate negative oxygen ions; and when the electrons of the carbon fiber mesh move outward, they can drive the electrons in the nano-tourmaline layer to move, so that more electrons in the nano-tourmaline layer are released, and the distance of electron release is increased, so that the distance of negative oxygen ion release is further, thereby increasing the range of action of the negative oxygen ion membrane of the present invention and improving the use efficiency.
[0041] On the other hand, the present invention adopts continuous carbon fiber 3D printing technology to continuously inject carbon fiber and reinforcing resin into a 3D printer to print a grid structure with a continuous carbon fiber reinforced structure, so that the negative oxygen ion membrane of the present invention has high strength and light weight. In addition, 3D printing technology can manufacture grid structures with complex geometric shapes, optimize product performance, and meet personalized needs. At the same time, the preparation method of the present invention directly prints physical parts from digital models, reduces the grid preparation process, and can reduce manufacturing steps and time.
[0042] In addition, the present invention uses a carbon fiber mesh, which has excellent thermal insulation performance and strength. In various fields, the thermal insulation problem has always been an important and difficult challenge to solve. Traditional thermal insulation materials have limitations in terms of weight, thickness and cost, and the carbon fiber mesh is arranged on the negative oxygen ion membrane of the present invention, which not only makes the negative oxygen ion membrane of the present invention have high strength and protects the glass from external impact, scratches and other damage; it can also effectively block external heat transfer, reduce temperature, and improve environmental comfort.
[0043] In addition, the provision of the carbon fiber mesh prolongs the service life of the negative oxygen ion membrane of the present invention, reduces the replacement frequency, and reduces the maintenance cost. The carbon fiber mesh has excellent permeability, can prevent the glass from fogging, and improve the light transmission efficiency of the glass. The carbon fiber mesh is more environmentally friendly than traditional film materials, and its production process has less impact on the environment.
[0044] The present invention arranges an optical conductive silver adhesive layer on the carbon fiber mesh, the optical conductive silver adhesive layer is added with high-refractive glass microbeads and conductive silver powder materials, has unique high conductivity and high light refractive index characteristics, and makes up for the defect that the carbon fiber mesh affects part of the light transmittance efficiency.
[0045] Therefore, the negative oxygen ion membrane of the present invention can release more negative oxygen ions farther, and at the same time has good strength and light transmittance, which can effectively improve the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0047] Figure 1 Schematic diagram of the structure of the electron resonance layer in Example 1;
[0048] Figure 2 It is a schematic diagram of the structure in which the electron resonance layer is connected to the PET film layer;
[0049] Figure 3 Schematic diagram of the structure of the negative oxygen ion membrane in Example 5;.
[0050] Marks and corresponding parts names in the attached drawings:
[0051] 1-PET film layer, 2-electronic resonance layer, 3-nano tourmaline layer, 4-polyurethane film layer, 5-protective layer, 6-carbon fiber mesh, 7-thin film solar cell, 8-optical conductive silver glue layer. DETAILED DESCRIPTION
[0052] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0053] In the description of the present invention, it should be understood that the terms "front", "rear", "left", "right", "up", "down", "vertical", "horizontal", "high", "low", "inside", "outside", etc., indicating directions or positional relationships are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as limiting the scope of protection of the present invention.
[0054] Example 1
[0055] The negative oxygen ion membrane of the present invention comprises an electron resonance layer 2, wherein the electron resonance layer 2 is as follows: Figure 1 As shown, the electron resonance layer 2 includes a grid-shaped carbon fiber mesh 6 , on which a plurality of thin film solar cells 7 are arranged, and electrodes of the plurality of thin film solar cells 7 are respectively connected to the carbon fiber mesh 6 .
[0056] In some embodiments, a plurality of thin-film solar cells 7 are respectively disposed at the cross-sections of the carbon fiber mesh 6 , and electrodes of the thin-film solar cells 7 are respectively connected to two ends of the carbon fiber mesh 6 .
[0057] The thin film solar cell 7 transmits part of the sunlight and absorbs part of the light for photoelectric conversion.
[0058] The thin-film solar cell 7 directly converts sunlight into electrical energy to heat the carbon fiber mesh 6. When the carbon fiber mesh 6 is subjected to thermal energy, its surface electrons will obtain enough energy to break free from the bondage and form free electrons. These free electrons will combine with oxygen molecules in the air to form negative oxygen ions.
[0059] The thin film solar cell 7 performs photoelectric conversion, generating a weak current on the carbon fiber mesh 6. Under the action of the weak current, the electrons of the carbon fiber mesh 6 are stimulated to resonate through electromagnetic waves, and the electrons of the carbon fiber mesh 6 are precipitated to form negative oxygen ions.
[0060] At the same time, the carbon fiber mesh 6 has excellent thermal insulation performance and strength. Traditional thermal insulation materials have limitations in weight, thickness and cost, while the carbon fiber mesh 6 of the present invention improves the thermal insulation performance and strength of the negative oxygen ion membrane, reduces the thickness and cost of the negative oxygen ion membrane, and the carbon fiber mesh 6 converts thermal energy into negative oxygen ion energy, increases the oxygen ion concentration, effectively blocks external heat transfer, and improves environmental comfort.
[0061] The carbon fiber net 6 is a mesh structure woven from a single strand or multiple strands of carbon fiber to obtain a grid-shaped carbon fiber net 6 .
[0062] Example 2
[0063] On the basis of the above-mentioned embodiment, the negative oxygen ion membrane of the present invention further comprises a nano-tourmaline layer 3, and the electron resonance layer 2 and the nano-tourmaline layer 3 are connected.
[0064] When the thin-film solar cell 7 directly converts sunlight into electrical energy, the thin-film solar cell 7 generates a weak electromagnetic field. Under the action of the magnetic field, the electrons in the tourmaline in the nano-tourmaline layer 3 resonate and move, thereby forming an electric current, activating the ions in the negative oxygen ion membrane of the present invention, causing it to release more negative oxygen ions.
[0065] Moreover, the thin film solar cell 7 is electrically connected to the carbon fiber net 6 to form a loop, and the nano-tourmaline layer 3 will generate a weak electromagnetic field and a thermoelectric field effect. When the surface electrons of the carbon fiber net 6 are freed from the bondage by the heat energy, the electrons in the nano-tourmaline layer 3 will be driven to move, thereby causing the molecules in the nano-tourmaline layer 3 to move farther, so that a larger area has negative oxygen ions, and the release amount of negative oxygen ions is further increased.
[0066] In some embodiments, the nano-tourmaline layer is composed of nano-tourmaline powder.
[0067] Example 3
[0068] On the basis of the above embodiment, an optically conductive silver glue layer 8 is provided on the carbon fiber mesh 6 , and the optically conductive silver glue layer 8 is connected to the electrodes of the thin-film solar cell 7 .
[0069] The optical conductive silver adhesive layer 8 includes a special type of conductive adhesive, which is mainly used for electrical connection between optical elements. It not only has good electrical conductivity, but also has good bonding strength and high temperature resistance. Preferably, the optical conductive silver adhesive layer 8 is an optical transparent tape, which is also a form of optical conductive silver adhesive, mainly used for the protection of optical elements, and has good transparency and adhesion.
[0070] In some embodiments, the optical conductive silver paste layer 8 includes high-refractive glass beads and conductive silver powder materials, which have unique high conductivity and high light refractive index characteristics, making up for the defect that the carbon fiber grid affects the partial light transmission efficiency. Among them, the high-refractive glass beads play a role in enhancing the refraction and reflection of light in the optical conductive silver paste, which helps to improve the transmission efficiency and optical performance of light. Conductive silver powder is the key component to achieve conductive properties. Through the high conductivity of silver powder, the optical conductive silver paste has good conductivity and can meet the needs of electronic components in high current environments.
[0071] At the same time, the optical conductive silver glue layer 8 is electrically connected through the thin film solar cell 7, and the electric energy of the thin film solar cell 7 acts on the carbon fiber mesh 6, so that the carbon fiber mesh 6 is better affected by the thermal energy, thereby improving the electron mobility of the carbon fiber mesh 6 and the nano-tourmaline layer 3.
[0072] Example 4
[0073] Based on the above embodiments, Figure 2 As shown, a PET film layer 1 is connected below the electron resonance layer 2. The PET film has excellent durability, tear resistance, heat resistance, water resistance and transparency. The negative oxygen ion membrane of the present invention can have a better light transmission effect when used. Preferably, the mesh area in the carbon fiber mesh 6 is larger than the area of the thin film solar cell 7.
[0074] Example 5
[0075] Based on the above embodiments, Figure 3 As shown, a polyurethane film layer 4 is connected to the top of the nano-tourmaline layer 3. A protective layer 5 is connected to the top of the polyurethane film layer 4.
[0076] A preparation process of a high-efficiency negative oxygen ion membrane comprises the following steps:
[0077] A single or multiple carbon fiber filaments and resin are continuously injected into a 3D printer, and printed into a grid shape on the PET film layer 1 to obtain a carbon fiber mesh 6;
[0078] The back of the thin film solar cell 7 is coated with adhesive and adhered to the cross of the carbon fiber mesh 6, with the electrode of the thin film solar cell 7 facing upward;
[0079] The optical conductive silver paste material is printed on the carbon fiber mesh 6 by using a 3D printer, and the optical conductive silver paste material is respectively connected to the electrodes of the thin film solar cell 7 to obtain the electron resonance layer 2;
[0080] The nano-tourmaline layer 3 is connected to the electron resonance layer 2 to obtain a negative oxygen ion membrane.
[0081] Wherein, the nano-tourmaline layer 3 comprises the following preparation steps:
[0082] Preparation of tourmaline ultrafine powder;
[0083] Select crystalline tourmaline ore, remove impurities until the purity reaches more than 95%, crush it to 1-10cm with a crocodile crusher, crush it into more than 300 meshes with a drum ball mill, and then use a stirring ball mill to ultrafinely grind it to D50≤1 micron, dry it, grind it with a hammer mill, and grind it with a jet mill to obtain deagglomerated tourmaline ultrafine powder with D50≤1 micron;
[0084] Tourmaline ultrafine powder, cerium oxide, yttrium oxide, neodymium oxide and titanium dioxide are dispersed by a jet mill, fully mixed, and calcined at 600° C. for 4 hours to obtain a semi-finished product, which is crushed by a jet mill until D50 is ≤ 2 microns to obtain high negative ion tourmaline powder; wherein the powder comprises the following parts by weight: 70 parts of tourmaline ultrafine powder, 5 parts of cerium oxide, 2 parts of yttrium oxide, 10 parts of neodymium oxide and 13 parts of titanium dioxide.
[0085] The high negative ion tourmaline powder, alcohol-water mixture, nanocellulose, silicon oxide, menthol solution and essence solvent are uniformly mixed, and the tourmaline transparent slurry is obtained by ball milling;
[0086] The tourmaline transparent slurry is coated on the electron resonance layer 2 to obtain the nano-tourmaline layer 3 .
[0087] The polyurethane film layer 4 and the protective layer 5 are sequentially connected on the nano-tourmaline layer 3 to obtain Figure 3 Negative oxygen ion membrane shown.
[0088] In some embodiments, the protective layer 5 is scratch-resistant and may be made of polypropylene (PP) or other polymers.
[0089] The term “connected” used herein, unless otherwise specified, may refer to a direct connection or an indirect connection via other components.
[0090] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-efficiency negative oxygen ion membrane, characterized in that: From bottom to top, it comprises an electron resonance layer (2) and a nano-tourmaline layer (3), the electron resonance layer (2) comprises a grid-shaped carbon fiber net (6), a plurality of thin-film solar cells (7) are arranged on the carbon fiber net (6), and electrodes of the plurality of thin-film solar cells (7) are respectively connected to the carbon fiber net (6).
2. A high-efficiency negative oxygen ion membrane according to claim 1, characterized in that: An optically conductive silver adhesive layer (8) is arranged on the carbon fiber mesh (6), and the optically conductive silver adhesive layer (8) is connected to the electrode of the thin-film solar cell (7).
3. A high-efficiency negative oxygen ion membrane according to claim 1, characterized in that: A plurality of thin-film solar cells (7) are arranged at the cross-sections of the carbon fiber mesh (6).
4. A high-efficiency negative oxygen ion membrane according to claim 1, characterized in that: A PET film layer (1) is connected below the electron resonance layer (2).
5. A high-efficiency negative oxygen ion membrane according to claim 1, characterized in that: A polyurethane film layer (4) is connected above the nano-tourmaline layer (3).
6. A high-efficiency negative oxygen ion membrane according to claim 5, characterized in that: A protective layer (5) is connected above the polyurethane film layer (4).
7. A high-efficiency negative oxygen ion membrane according to claim 1, characterized in that: The mesh area in the carbon fiber net (6) is larger than the area of the thin-film solar cell (7).
8. A process for preparing a highly efficient negative oxygen ion membrane, characterized in that: The following steps are involved: Continuously injecting a single or multiple carbon fiber filaments and resin into a 3D printer, and printing them into a grid shape on the PET film layer (1) to obtain a carbon fiber mesh (6); The back of the thin-film solar cell (7) is coated with adhesive and adhered to the cross-section of the carbon fiber net (6), with the electrode of the thin-film solar cell (7) facing upwards; An optically conductive silver paste material is printed on a carbon fiber mesh (6) using a 3D printer, and the optically conductive silver paste material is respectively connected to electrodes of a thin-film solar cell (7) to obtain an electronic resonance layer (2); A nano-tourmaline layer (3) is connected to the electron resonance layer (2) to obtain a negative oxygen ion membrane.
9. The process for preparing a high-efficiency negative oxygen ion membrane according to claim 8, characterized in that: The nano-tourmaline layer (3) comprises the following preparation steps: Preparation of tourmaline ultrafine powder; After fully mixing tourmaline ultrafine powder, cerium oxide, yttrium oxide, neodymium oxide and titanium dioxide, calcining at high temperature to obtain a semi-finished product, and crushing the semi-finished product to obtain high negative ion tourmaline powder; The high negative ion tourmaline powder, alcohol-water mixture, nanocellulose, silicon oxide, menthol solution and essence solvent are uniformly mixed, and the tourmaline transparent slurry is obtained by ball milling; The tourmaline transparent slurry is coated on the electron resonance layer (2) to obtain the nano tourmaline layer (3).
10. The process for preparing a high-efficiency negative oxygen ion membrane according to claim 9, characterized in that: A polyurethane film layer (4) and a protective layer (5) are sequentially connected to the nano-tourmaline layer (3) to obtain a negative oxygen ion membrane.
Citation Information
Patent Citations
High negative ion tourmaline powder and preparation method thereof
CN101450845A
Stable tourmaline slurry and preparation method thereof
CN108609999A
Solar heating and thermal protection clothes
CN201332701Y
Far infrared heating membrane
CN201862151U
Warm device of system
CN207763035U